2021
DOI: 10.1016/j.drugalcdep.2020.108488
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and mental health during COVID-19 lockdown: A cross-sectional study in a sample of UK adults

Abstract: Highlights More than one in six UK adults increased their alcohol consumption during lockdown. Increased alcohol consumption was associated with poor overall mental health. These findings highlight the importance of planning targeted support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
156
12
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(201 citation statements)
references
References 19 publications
29
156
12
4
Order By: Relevance
“…This aligns with prior research describing smokers becoming overwhelmed with boredom due to being confined to their homes and having reduced social interactions [38] and boredom playing a crucial role in predicting cessation outcomes [39,40]. The confines of lockdown have the potential for harmful behavior such as increased alcohol consumption [41] in some and self-improvement behavior in others. Indeed, one participant viewed this period of confinement as the perfect opportunity to make a quit attempt.…”
Section: Discussionsupporting
confidence: 86%
“…This aligns with prior research describing smokers becoming overwhelmed with boredom due to being confined to their homes and having reduced social interactions [38] and boredom playing a crucial role in predicting cessation outcomes [39,40]. The confines of lockdown have the potential for harmful behavior such as increased alcohol consumption [41] in some and self-improvement behavior in others. Indeed, one participant viewed this period of confinement as the perfect opportunity to make a quit attempt.…”
Section: Discussionsupporting
confidence: 86%
“…There are several reasons why alcohol consumption may increase during the COVID-19 pandemic. These include boredom and disruption to routines caused by the lockdown, the threat of the disease, changes to life circumstances and associated distress [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 754 adults from the USA demonstrated that psychological distress caused by the COVID-19 pandemic was associated with increased alcohol consumption, whereas the perceived threat from the virus itself was not associated with increased alcohol consumption [ 31 ]. Other reasons people drink during a crisis include the inhibiting effect of alcohol on the nervous system offering temporary relief from emotions, anxiety, anger, sleep disorders, depression and post-traumatic stress disorders associated with a lockdown [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, constraining daily routines and limited access to typical social or environmental reinforcement sources may increase the risk of engaging with non-healthy strategies to cope with the pandemic, such as eating more unhealthy food and drinking more alcohol than usual [ 6 , 7 , 8 , 9 , 28 ], especially for women. Although previous cross-sectional studies have found an increase in these high-risk behaviors [ 29 , 30 , 31 ], it is unclear what predicts these changes and, more importantly, if these behaviors are maintained over time. Since the pandemic has been found to increase levels of stress across the population, it will be necessary to evaluate changes over time in health-risk behaviors and their predictors, that are known to be affected by stress [ 32 ].…”
Section: Introductionmentioning
confidence: 99%